2009
DOI: 10.1056/nejmoa0903068
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Antibody Associated with Autoimmune Pancreatitis

Abstract: The antibody that we identified was detected in most patients with autoimmune pancreatitis but also in some patients with pancreatic cancer, making it an imperfect test to distinguish between these two conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
212
4
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(231 citation statements)
references
References 24 publications
3
212
4
10
Order By: Relevance
“…However, they did not confirm that the IgG subclass of those antigens was IgG4. In contrast, Frulloni et al demonstrated that the antibodies against an amino acid sequence of plasminogen-binding protein of Helicobacter pylori were frequently found in the sera of autoimmune pancreatitis, although this interesting finding has not yet been confirmed by others [32]. Similarly, we previously showed the possibility of involvement of Mycobacterium tuberculosis in the pathogenesis of IgG4-RD [33].…”
Section: Detection Of Identical or Genetically Related Clones Betweencontrasting
confidence: 65%
“…However, they did not confirm that the IgG subclass of those antigens was IgG4. In contrast, Frulloni et al demonstrated that the antibodies against an amino acid sequence of plasminogen-binding protein of Helicobacter pylori were frequently found in the sera of autoimmune pancreatitis, although this interesting finding has not yet been confirmed by others [32]. Similarly, we previously showed the possibility of involvement of Mycobacterium tuberculosis in the pathogenesis of IgG4-RD [33].…”
Section: Detection Of Identical or Genetically Related Clones Betweencontrasting
confidence: 65%
“…Immunoglobulin G-4 disease represents a unique inflammatory condition that induces tumorous swelling of affected organs, histologically characterized with diffuse lymphoplasmacytic infiltration of affected organ, occasional eosinophils, storiform fibrosis, obliterative phlebitis, infiltration by numerous IgG4-bearing plasma cells, and marked clinically by dramatic response to steroid therapy [53]. Autoimmune pancreatitis (AIP) seems to be the prototype of an IgG4-related disease, suggesting that gastric H. pylori infection triggers AIP in genetically predisposed individuals through molecular mimicry with plasminogen-binding protein of H. pylori exhibiting homology to ubiquitin-protein ligase E3 component n-recognin 2, an enzyme expressed in pancreatic acinar cells [54]. However, serum IgG4 levels were elevated in only 53% of patients in the mentioned study, suggesting that the cohort assessed might, in substantial part, represent non-IgG4-related AIP (type II AIP).…”
Section: Ophthalmology Skin and Oral Mucosa Diseasesmentioning
confidence: 99%
“…Frulloni L et al reported a novel serologic marker of AIP, antibodies against plasminogenbinding protein (Anti-PBP) peptide, which was present in 94% of AIP patients and in no health controls. However, in this study, these Anti-PBP peptide antibodies were also present in 5% of the patients with PC [12]. The most significant finding on an ERCP or magnetic resonance cholangiopancreatography (MRCP) includes a diffuse, irregular narrowing of the pancreatic duct; a narrowed main and dorsal pancreatic duct, or a focal stricture of the pancreatic duct [13].…”
Section: Discussionmentioning
confidence: 52%